Nurses’ Perception of Disaster Preparedness in Bandung - Kosasih, Cecep Eli; Solehati, Tetti; Trisyani, Yanny; Budiman, Ganjar Wisnu (GLOBAL HEALTH SCIENCE GROUP, 2024)
Indonesia as an archipelagic country has various natural and non-natural disasters, the preparedness of health workers, especially nurses, influences disaster management, where nurses have the largest number during disaster management. Objective to identify nurses' perceptions of nurse preparedness in the pre-disaster, disaster, and post-disaster phases in the Bandung City area. The type of research used is descriptive quantitative survey research. The population is all nurses in the West Java region who are adults. The sampling technique used in this study uses convenience sampling. Respondents were nurses in Bandung, a total of 287 people. Data was collected by filling out a questionnaire using Google Forms. The data obtained was then analyzed univariately using descriptive analysis through frequencies and percentages. The results showed that most (80.5%) of disaster education and training was lacking, and a small proportion (19.5%) were good. More than half (54.7%) of knowledge and information about disasters needs to be improved, and almost half (45.3%) is good. Handling of bioterrorism and emergency response Most (61.3%) are poor, and almost half (38.7%) are good. Nurses' response during a disaster was more than half (51.2%) poor, and almost half (48.8%) were good. During the disaster evaluation, more than half (51.2%) were poor, and almost half (48.8%) were good. Overall, the perception of disaster preparedness is more than half (50.4%) poor, and almost half (49.6%) is good. Nurses' perceptions of disaster preparedness in some aspects are still lacking, and some are good.